PENGARUH PARIWISATA, INVESTASI PMDN, DAN INVESTASI PMA TERHADAP PDRB ADHB TINGKAT KABUPATEN PROVINSI BANTEN - Desmintari Desmintari; Lina Aryani (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
This study aims to find out how the influence of Tourism, Foreign Direct Investment, and Domestic Investment to GDRP Banten Province. The analysis used panel data, t test, f test and calculating the value of the coefficient of determination and correlation using Eviews 9. The research results obtained that the tourism variable has not significant effect on GDRP while the Foreign Direct Investment and Domestic Investment has effect and significance on GDRP. Adjusted R2 Tourism, Foreign Direct Investment and Domestic Investment on GDRP is 0.71.